Intensive care unit nurses living through COVID‐19: A qualitative study. (21st May 2021) - Cadge, Wendy; Lewis, Mariah; Bandini, Julia; Shostak, Sara; Donahue, Vivian; Trachtenberg, Sophie; Grone, Katelyn; Kacmarek, Robert; Lux, Laura; Matthews, Cristina; McAuley, Mary Elizabeth; Romain, Frederic; et al.
Abstract: Aims: To understand how nurses experience providing care for patients hospitalized with COVID‐19 in intensive care units. Background: As hospitals adjust staffing patterns to meet the demands of the pandemic, nurses have direct physical contact with ill patients, placing themselves and their families at physical and emotional risk. Methods: From June to August 2020, semi‐structured interviews were conducted. Sixteen nurses caring for COVID‐19 patients during the first surge of the pandemic were selected via purposive sampling. Participants worked in ICUs of a quaternary 1, 000‐bed hospital in the Northeast United States. Interviews were transcribed verbatim, identifiers were removed, and data were coded thematically. Results: Our exploratory study identified four themes that describe the experiences of nurses providing care to patients in COVID‐19 ICUs during the first surge: (a) challenges of working with new co‐workers and teams, (b) challenges of maintaining existing working relationships, (c) role of nursing leadership in providing information and maintaining morale and (d) the importance of institutional‐level acknowledgement of their work. Conclusions: As the pandemic continues, hospitals should implement nursing staffing models that maintain and strengthen existing relationships to minimize exhaustion and burnout. Implications for Nursing Management: To better support nurses, hospital leaders need to account for their experiences caring for COVID‐19 patients when making staffing decisions.